Lindera aggregata (Sims) Kosterm: a systematic review of its traditional applications, phytochemical and pharmacological properties, and quality control - Qinger Huang; Kaohua Liu; Luping Qin; Bo Zhu (Medicinal Plant Biology, 2023)
Lindera aggregata (Sims) Kosterm (LA), a traditional medicinal herb, has long been used as a regulator of 'Qi' (vital energy) in China, for treating chest and abdominal pain, bladder deficiency, hernia, bladder cold, dysmenorrhea, and frequent enuresis and urination. This article describes a systematic review of botanical characteristics, traditional applications, and phytochemical, pharmacological, pharmacokinetic, and toxicological properties of LA through the collation and discussion of literature from several databases, namely Elsevier, Web of Science, SciFinder, PubMed, CNKI, ScienceDirect, and Google Scholar, as well as Master's theses and Doctoral dissertations. To date, over 166 chemical components have been isolated from LA, including alkaloids, sesquiterpenoids, flavonoids, cyclopentanedione derivatives and enantiomers of ketone derivatives, disesquiterpenoid-geranylbenzofuranone conjugates, benzenoids, and benzenoid glycosides. Crude extracts of LA and its purified compounds are used for treating inflammation, tumor, hyperlipidemia, alcoholic liver disease, diarrhea, abdominal pain, and antibiotics; these extracts and compounds possess broad pharmacological properties with anti-inflammatory activity, liver protection effects, antitumor effects, lipid lowering effects, antibacterial and analgesic effects, and kidney protection activity. Additional studies are needed to confirm the relationship between the traditional effects of LA and modern pharmacological research. Hence, we suggest that future investigations on LA should focus on modern pharmacological research to confirm or support its traditional application.